SEMIOTIC STUDY OF TETRALOGY LASKAR PELANGI COVER DESIGN NOVEL BOOK BY ANDREA HIRATA - IRMA OCTAVIANI, Drs. Syafwan, M.Si., Hendra Afriwan, S.Sn., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The purpose of this study were to: (1) describe icon, symbol, index that appear in design book cover Tetralogy of Novel Laskar Pelangi by Andrea Hirata and (2) describe visual element that appear in design book cover of Novel Laskar Pelangi by Andrea Hirata.This research used a qualitative with descriptive intrepretative method, the data collected in the form of word and images and then explained the meaning with interpretation or construe in paragraph and in table form. Data source obtained from: (1) Laskar Pelangi, (2) Sang Pemimpi, (3) Edensor, and (4) Maryamah Karpov by Andrea Hirata that published by Penerbit Bentang. The theory used is the semiotic by Peirce who divide between sign and referent into three categories: icon, symbol and index is a sign that the related between the marker and the marker is the same shape.Key Word: Design, Cover, Visual, Semotic